Diseño de un prototipo de aplicación móvil para el ingreso en el parqueadero vehicular de la Cooperativa de Transportes Loja, de la ciudad de Loja - Quezada Ríos, Ángel Enrique (2022)
The increase in the supply of parking lots in some cities in Ecuador, specifically in Loja, has been motivated by the increase in the number of vehicles. In addition, the urban regeneration project implemented in the city of Loja has significantly reduced the number of public parking spaces, resulting in the existence of 52 private parking lots distributed in the center of the city of Loja. Of these parking lots, 90% do not use technological tools to manage the parking lot service, due to lack of knowledge or bad experiences, while the remaining 10% have a computerized system for managing the vehicle parking lot, whose common denominator is the issuance of tickets to record entry and exit. Based on this reality, this degree work, tries to support the balance that should exist in the environment, to take care of the few natural resources that people have, providing a prototype of mobile application called LojIn, which allows the entrance to the parking lot of the Loja transport cooperative, without the need to print tickets, as it is being done at present. To achieve this objective, we used the agile methodology for software development called Extreme Programming (XP), which resulted in a planning product, a list of requirements, user stories, and the LojIn mobile application prototype, in addition to an active iteration with the client, and to perform functionality tests in short times. The logical design pattern used is BLOC (Business Logic Component). Finally, the evidenced operation of the LojIn mobile application prototype represents a friendly and sustainable contribution to the environment, since it avoids the printing of tickets to enter the parking lot of the Cooperativa de Transportes Loja. Keywords: Vehicle parking, mobile application, barcode, Flutter.